Regional cooperation- research & capacity building ecosystems (African Journal of Public Administration & Management, 2026)
Working at the ecosystem level to support resource mobilisation for researchinfrastructure. Capacity development for researchers, including emerging researchers. Research Associates onboarding. Continental-wide Research Networks. Public Lectures, Webinars, Colloquiua